On the heapability of finite partial orders - Balogh, János; Bonchiş, Cosmin; Diniş, Diana; Istrate, Gabriel; Todinca, Ioan (Discrete mathematics and theoretical computer science, 2020)
We investigate the partitioning of partial orders into a minimal number of heapable subsets. We prove a characterization result reminiscent of the proof of Dilworth's theorem, which yields as a byproduct a flow-based algorithm for computing such a minimal decomposition. On the other hand, in the particular case of sets and sequences of intervals we prove that this minimal decomposition can be computed by a simple greedy-type algorithm. The paper ends with a couple of open problems related to the analog of the Ulam-Hammersley problem for decompositions of sets and sequences of random intervals into heapable sets.